Cover Picture: Contrib. Plasma Phys. 2/2016. Issue 2 (February 2016) - Unknown
Abstract: Images of the plasma jet in a 500 μm quartz tube at F r = 20, 100 and 500 sccm and at V A = 20 kV. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)